2008
DOI: 10.5194/npg-15-903-2008
|View full text |Cite
|
Sign up to set email alerts
|

Study of nonlinear ion- and electron-acoustic waves in multi-component space plasmas

Abstract: Abstract. Large amplitude ion-acoustic and electronacoustic waves in an unmagnetized multi-component plasma system consisting of cold background electrons and ions, a hot electron beam and a hot ion beam are studied using Sagdeev pseudo-potential technique. Three types of solitary waves, namely, slow ion-acoustic, ion-acoustic and electron-acoustic solitons are found provided the Mach numbers exceed the critical values. The slow ion-acoustic solitons have the smallest critical Mach numbers, whereas the electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
57
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 103 publications
(58 citation statements)
references
References 56 publications
0
57
1
Order By: Relevance
“…The electron acoustic instability will lead to enhancements (Berthomier et al, 2000) or decreases in electron density, as opposed to holes in electron phase space. Recently, Lakhina et al (2008b) have developed a model to study large amplitude ion-acoustic and electronacoustic waves in an unmagnetized multi-component plasma system consisting of cold background electrons and ions, a hot electron beam and a hot ion beam. For typical parameters of the plasma sheet boundary layer (Grabbe and Eastman, 1984), the model predicted positive potential slow ionacoustic, ion-acoustic and electron-acoustic solitons.…”
Section: Discussion Of Esw Generation Mechanismsmentioning
confidence: 99%
“…The electron acoustic instability will lead to enhancements (Berthomier et al, 2000) or decreases in electron density, as opposed to holes in electron phase space. Recently, Lakhina et al (2008b) have developed a model to study large amplitude ion-acoustic and electronacoustic waves in an unmagnetized multi-component plasma system consisting of cold background electrons and ions, a hot electron beam and a hot ion beam. For typical parameters of the plasma sheet boundary layer (Grabbe and Eastman, 1984), the model predicted positive potential slow ionacoustic, ion-acoustic and electron-acoustic solitons.…”
Section: Discussion Of Esw Generation Mechanismsmentioning
confidence: 99%
“…This is a convincing indicator of the presence of nonlinear electron acoustic waves which consist of solitary waves leading to electron phase space holes generation with much lower threshold for excitation than ordinarily believed [Berthomier et al, 2000;Lakhina et al, 2008aLakhina et al, , 2008b.…”
Section: Generation Of Solitary Wavesmentioning
confidence: 99%
“…It was shown that the associated nonlinear structures can either couple to kinetic Alfvén waves or can lead to the formation of bipolar pulses in the electric field identified as electron holes [Berthomier et al, 2000;Berthomier et al, 2003;Shukla et al, 2004;Singh and Lakhina, 2004;Kakad et al, 2007;Lakhina et al, 2008aLakhina et al, , 2008bSingh et al, 2009].…”
Section: Frequency and Growth Ratementioning
confidence: 99%
“…One can recover Equation (7) 17). But both these forms of Sagdeev potential cannot handle a cold (T ¼ 0) plasma species, and are inferior to the expression of Sagdeev potential as given in a series of paper by Lakhina et al [10][11][12]15,16 which can handle cold as well as warm plasma species, but then here, one needs to keep track of proper signs for the density expressions for different plasma species.…”
mentioning
confidence: 99%
“…[10][11][12][13] The idea of writing the Sagdeev potential with a unique sign for plasma species grew when we came across the work of Ghosh et al 14 who presented densities in a different way than given in our earlier papers. 15,16 Equation (6) in Ref. 1 is written in the form first given by Ghosh et al 14 If one considers the lower sign (i.e., minus sign) in this equation, and do the symbolic algebraic operation on the terms under the square root, all densities regain their equilibrium value when U ¼ 0.…”
mentioning
confidence: 99%